Efeito in vitro da sertralina isolada e associada a antifúngicos e sua ação sobre biofilme em cepas de Candida spp. - Rodrigues, Daniel Sampaio (2023)
Fungal infections have become a serious public health problem, mainly associated to patients with risk factors such as long periods of hospitalization, in intensive care units, use of immunomodulatory therapies, and HIV carriers. Among these, Candida spp. stands out for its high prevalence compared to other pathogenic fungi, described as the fourth causative agent of blood stream infections, and a mortality rate reaching 70%. Its ability to develop resistance toavailable antifungals is a growing concern, as their number is reduced compared to antibacterials, which may be due to different mechanisms, including biofilm formation. Thus, the development of new antifungal therapeutic possibilities that present activity not only in planktonic cells, but also in biofilms, becomes a priority, where drug repositioning and combined therapy prove to be viable options, as they reduce the time and cost of new drugs developing. The antifungal activity of selective serotonin reuptake inhibitor antidepressant drugs against Candida spp. strains is described in the literature, and indicate that sertraline has an effect on this microorganism at low concentrations, however, few studies have explored its potential. The present work aimed to investigate the in vitro activity of SER againstsensitive and resistant to fluconazole Candida spp. strains, in its planktonic form and in biofilm. The inhibitory effect of sertraline was evaluated according to the broth microdilution standard methodology as indicated in the document M27-A3 of the Clinical & Laboratory Standards Institute, the type of drug interaction with fluconazole, itraconazole and amphotericin B by the checkerboard method and the index fractional inhibitory concentration, in addition to determining the effect on Candida spp. by the relationship between minimum fungicidal concentration and minimum inhibitory concentration. The mechanism of action was evaluated using flow cytometry and in silico assays. Finally, the activity of sertraline on Candida spp. was determined in vitro in a 96-well plate, for both matured and forming, and its cytotoxicity was investigated by the Alamar blue method in human lymphocyte cells. Sertraline presented MICs ranging from 2 to 16 µg/mL in Candida spp. planktonic cells with fungicidal effect, showing 93.75% of indifferent interactions with fluconazole, 37.5% additive and 25% synergistic with itraconazole, and 43.75% additive when combined with amphotericin B. The sertraline mechanism of action against strains ofCandidaspp. resistant to fluconazole seems to be related to the cell membrane and wall, inhibiting the biosynthesis of essential structural components. Its activity in biofilms also occurs at low concentrations, inhibiting more than 85% of the biofilm both matured and in formation, and all effective concentrations found were below the IC50, so its effect occurs at safe concentrations. Thus, we can see that sertraline is a potential antifungal for the treatment of infections caused by fluconazole-resistantCandida spp., showing an effect in safe concentrations both in planktonic cells and biofilm form.